2015
DOI: 10.5350/dajpn2015280105
|View full text |Cite
|
Sign up to set email alerts
|

Using basic number processing tasks in determining students with mathematics disorder risk

Abstract: Using basic number processing tasks in determining students with mathematics disorder riskObjective: This study investigated whether it was possible to determine the risk of having mathematics disorder with a simple screening tool containing four types of basic number processing tasks.Method: Mathematics Achievement Tests (MAT) and Basic Number Processing Tests (BNPT) were administered to a total of 487 students from first through fourth grade of 12 different elementary schools in Ankara, Turkey.Students with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The mastery of basic arithmetic skills is considered a key goal in early education (Göbel et al, 2014 ). Nevertheless, difficulties with calculation are typically recognized late in primary school (Olkun & Denizli, 2015 ), and children with such difficulties usually also have working memory deficits (Andersson & Lyxell, 2007 ; D’Amico & Guarnera, 2005 ). Although working memory has been recognized as a multidimensional concept, little research has considered which of the working memory components truly matter for arithmetic development, especially when children are at young ages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mastery of basic arithmetic skills is considered a key goal in early education (Göbel et al, 2014 ). Nevertheless, difficulties with calculation are typically recognized late in primary school (Olkun & Denizli, 2015 ), and children with such difficulties usually also have working memory deficits (Andersson & Lyxell, 2007 ; D’Amico & Guarnera, 2005 ). Although working memory has been recognized as a multidimensional concept, little research has considered which of the working memory components truly matter for arithmetic development, especially when children are at young ages.…”
Section: Introductionmentioning
confidence: 99%
“…They found that basic number processing directly accounted for those children’s poor performance in arithmetic operations and arithmetical strategy use. Additionally, basic number processing tasks such as number comparison tests and mental number line tests can be used as efficient screening tools to identify students at risk of dyscalculia (Olkun & Denizli, 2015 ).…”
Section: Introductionmentioning
confidence: 99%